Dietary Interventions Are Beneficial for Patients with Chronic Pain: A Systematic Review with Meta-Analysis. Issue 3 (17th November 2020) - Field, Rowena; Pourkazemi, Fereshteh; Turton, Jessica; Rooney, Kieron
Abstract: Background: The standard Western diet is high in processed hyperpalatable foods that displace nutrient-dense whole foods, leading to inflammation and oxidative stress. There is limited research on how these adverse metabolic drivers may be associated with maladaptive neuroplasticity seen in chronic pain and whether this could be attenuated by a targeted nutritional approach. The aim of this study was to review the evidence for whole-food dietary interventions in chronic pain management. Method: A structured search of eight databases was performed up to December 2019. Two independent reviewers screened studies and evaluated risk of bias by using the National Institutes of Health assessment tool for controlled or pre–post studies and the Joanna Briggs checklist for case reports. A meta-analysis was performed in Review Manager. Results: Forty-three studies reporting on 48 chronic pain groups receiving a whole-food dietary intervention were identified. These included elimination protocols (n = 11), vegetarian/vegan diets (n = 11), single-food changes (n = 11), calorie/macronutrient restriction (n = 8), an omega-3 focus (n = 5), and Mediterranean diets (n = 2). A visual analog scale was the most commonly reported pain outcome measure, with 17 groups reporting a clinically objective improvement (a two-point or 33% reduction on the visual analog scale). Twenty-seven studies reported significant improvement on secondary metabolic measures. Twenty-five groups were included in a meta-analysis that showed a significant finding for the effect of diet on pain reduction when grouped by diet type or chronic pain type. Conclusion: There is an overall positive effect of whole-food diets on pain, with no single diet standing out in effectiveness. This suggests that commonalities among approaches (e.g., diet quality, nutrient density, weight loss) may all be involved in modulating pain physiology. Further research linking how diet can modulate physiology related to pain (such as inflammation, oxidative stress, and nervous system excitability) is required.